Physicochemical characterization of bunches from American oil palm (Elaeis oleifera H.B.K. Cortes) and their hybrids with African oil palm (Elaeis guineensis Jacq.) (2018)
The aim of this study was to carry out a comparative analysis of physical and chemical traits of bunches from genotypes of Elaeis oleifera and their interspecific hybrids OxG with Elaeis guineensis, establishing values in bunch components and oil potential, as well as oil quality by analyzing fatty acids, vitamin E and carotenes content. Bunches stemmed from inflorescences without assisted pollination and perimeter presence of E. guineensis. The experimental design used, was a completely randomized experimental design with three experimental units, each comprised of three bunches. E. oleifera Sinú genotype (76.53 %) and OxG hybrid II (72.64 %) obtained the highest fruit set. Regarding oil extraction potential, values were higher in OxG hybrids, finding in hybrid II an outstanding value (20.82%). E. oleifera materials showed better fatty acids profiles with the Sinú genotype being the most prominent material with 79.1 % of unsaturated fatty acids, together with hybrid II (70.2 %). Regarding vitamin E content, we confirmed that E. oleifera possesses high quality oil especially for genotype Coarí (1,006.7 ppm) and hybrid II (1,549.6 ppm); furthermore, genotype Sinú was the one with the highest total carotene content (1,524.7 ppm).